Professional Development and Training for Young Teachers in Russia - Мarina Pinskaya; Alena Ponomareva; Sergey Kosaretsky (Voprosy obrazovaniya / Educational Studies Moscow, 2016)
Based on TALIS‑2013 results, we analyze professional competencies of young teachers in Russia, their employment patterns, introduction into the profession, professional development, the challenges the meet in teaching, and their satisfaction with the feedback they get from school administrators and colleagues. We show that the corpus of Russian teachers is not homogeneous, as assessments made by teachers of different age differ greatly in all areas. Young teachers have difficulties with professional communication and face barriers in accessing professional development. Meanwhile, they are not ready to solve practical teaching problems and have insufficient knowledge of modern teaching techniques. We come to the conclusion that young teachers need their professional growth opportunities to be extended, primarily through active group-based training. Their chances for successful adaptation to school practice requirements could be increased by establishing an introduction to the profession period to support their basic motivation and prevent the flight of young teachers from school due to low job satisfaction.